Understanding the electron transfer process in ZnO-naphthol azobenzoic acid composites from photophysical characterisation - George, Leena; Kunhikannan, Athira K.; Illathvalappil, Rajith; Ottoor, Divya; Kurungot, Sreekumar; Devi, R. Nandini (Physical Chemistry Chemical Physics, 2016)
Semiconductor nanoparticles surface modified with organic molecules capable of visible light absorption and effectively transferring the electrons to the catalytic sites have the potential to be good photocatalysts. ZnO nanoparticles of size similar to 3 nm are grafted with two azonaphthols, one conjugated and the other non-conjugated. The photophysical properties of modified ZnO indicate an effective electron transfer from the conjugated azonaphthol to ZnO but not in the case of the non-conjugated molecule. It is also observed from lifetime studies that the conjugated molecule stabilises the defect sites on ZnO nanoparticles. It is possible that excited electrons from the conjugated molecule are transferred to specific defect sites in ZnO. This apparently does not occur in the non-conjugated molecule, bringing to focus the importance of the photophysical characteristics of organic modifiers in designing visible light active photocatalysts.

Unravelling the mechanism of electrochemical degradation of PANI in supercapacitors: achieving a feasible solution - Sekar, Pandiaraj; Anothumakkool, Bihag; Vijayakumar, Vidyanand; Lohgaonkar, Apurva; Kurungot, Sreekumar (Chemelectrochem, 2016)
Herein, we have investigated the mode of electrochemical degradation of polyaniline (PANI) when it was utilized as electrodes for supercapacitors. The PANI-based electrodes in supercapacitor devices were biased at a constant potential of 0.80 V, and the performance characteristics and property changes were carefully investigated as a function of the difference in the polarity of the electrodes. Subsequent to this, the analysis of the individual electrodes [positive (POS-PANI) and negative (NEG-PANI)] shows that the degradation mainly occurs at POS-PANI in comparison to NEG-PANI. Moreover, NEG-PANI retains a maximum capacitance of 510 Fg(-1), with a low charge-transfer resistance (R-CT) of 1.84 Omega and similar redox behavior in comparison to the fresh PANI (f-PANI). In contrast to this case, POS-PANI shows significant loss in capacitance (250 Fg(-1)) and increase in R-CT (3.5 Omega) with a disappearance of the characteristic redox behavior normally displayed by PANI. Furthermore, the drastic drop in the electrical conductivity for POS-PANI (1.2 Scm(-1)) compared to f-PANI (3.4 Scm(-1) and NEG-PANI (2.4 Scm(-1)) shows that the degradation of PANI occurs mainly at the anode (POS-PANI) and, thus, contributes to reduce the net performance of the cell. Hence, to ensure this potential-induced degradation of PANI in supercapacitors and also to promote the system stability, we made an asymmetric supercapacitor (ASC) by keeping PANI as a negative electrode and using carbon as a positive electrode. The derived system is found to display stable capacitance behavior before and after the potential application, in contrast to the ASC fabricated by using conventional method, that is, by keeping PANI as the positive electrode and carbon as the negative electrode. Furthermore, the durability analysis of the prototype solid-state ASC shows an enhanced durability of 27000 cycles with excellent columbic efficiency. The findings of the present study will be helpful in the development of highly stable supercapacitors and other similar energy systems when a material like PANI should be utilized for the electrode applications.
Keywords: asymmetric supercapacitors; cycle stability; electrochemical degradation; polarization; redox chemistry

Ultrahigh ionic conduction in water-stable close-packed metal-carbonate frameworks - Manna, Biplab; Desai, Aamod V.; Illathvalappil, Rajith; Gupta, Kriti; Sen, Arunabha; Kurungot, Sreekumar; Ghosh, Sujit K. (Inorganic Chemistry, 2017)
Utilization of the robust metal-carbonate backbone in a series of water-stable, anionic frameworks has been harnessed for the function of highly efficient solid-state ion conduction. The compact organization of hydrophilic guest ions facilitates water-assisted ion-conduction in all the compounds. The dense packing of the compounds imparts high ion-conducting ability and minimizes the possibility of fuel crossover, making this approach promising for design and development of compounds as potential components of energy devices. This work presents the first report of evaluating ion-conduction in a purely metal-carbonate framework, which exhibits high ion-conductivity on the order of 10(-2) S cm(-1) along with very low activation energy, which is comparable to highly conducting well-known crystalline coordination polymers or commercialized organic polymers like Nafion.

Unravelling faradaic electrochemical efficiencies over Fe/Co spinel metal oxides using surface spectroscopy and microscopy techniques - Kashyap, Varchaswal; Pandikassala, Ajmal; Singla, Gourav; Khan, Tuhin Suvra; Haider, M. Ali; Vinod, C. P.; Kurungot, Sreekumar (Nanoscale, 2022)
Cobalt and iron metal-based oxide catalysts play a significant role in energy devices. To unravel some interesting parameters, we have synthesized metal oxides of cobalt and iron (i.e. Fe2O3, Co3O4, Co2FeO4 and CoFe2O4), and measured the effect of the valence band structure, morphology, size and defects in the nanoparticles towards the electrocatalytic hydrogen evolution reaction (HER), the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR). The compositional variations in the cobalt and iron precursors significantly alter the particle size from 60 to <10 nm and simultaneously the shape of the particles (cubic and spherical). The Tauc plot obtained from the solution phase ultraviolet (UV) spectra of the nanoparticles showed band gaps of 2.2, 2.3, 2.5 and 2.8 eV for Fe2O3, Co3O4, Co2FeO4 and CoFe2O4, respectively. Further, the valence band structure and work function analysis using ultraviolet photoelectron spectroscopy (UPS) and core level X-ray photoelectron spectroscopy (XPS) analyses provided better structural insight into metal oxide catalysts. In the Co3O4 system, the valence band structure favors the HER and Fe2O3 favors the OER. The composites Co2FeO4 and CoFe2O4 show a significant change in their core level (O 1s, Co 2p and Fe 2p spectra) and valence band structure. Co3O4 shows an overpotential of 370 mV against 416 mV for Fe2O3 at a current density of 2 mA cm(-2) for the HER. Similarly, Fe2O3 shows an overpotential of 410 mV against the 435 mV for Co3O4 at a current density of 10 mA cm(-2) for the OER. However, for the ORR, Co3O4 shows 70 mV improvement in the half-wave potential against Fe2O3. The composites (Co2FeO4 and CoFe2O4) display better performance compared to their respective parent oxide systems (i.e., Co3O4 and Fe2O3, respectively) in terms of the ORR half-wave potential, which can be attributed to the presence of the oxygen vacancies over the surface in these systems. This was further corroborated in density functional theory (DFT) simulations, wherein the oxygen vacancy formation on the surface of CoFe2O4(001) was calculated to be significantly lower (similar to 50 kJ mol(-1)) compared to Co3O4 (001). The band diagram of the nanoparticles constructed from the various spectroscopic measurements with work function and band gap provides in-depth understanding of the electrocatalytic process.

Unlocking the potential of proton conductivity in guanidinium-based ionic covalent organic nanosheets (iCONs) through pore interior functionalization - Kumar, Sushil; Hu, Jiahui; Pandikassala, Ajmal; Kurungot, Sreekumar; Addicoat, Matthew A.; Szekely, Gyorgy (Applied Materials Today, 2023)
Recently, scientists have been exploring the incorporation of proton carriers such as water and phosphoric acid (PA) into the pores and channels of porous materials to enhance proton conduction performance. Ionic covalent organic nanosheets (iCONs) have been identified as promising functional materials due to their inbuilt ionic interfaces, which can facilitate strong interaction with counter ions present inside the pore structure and thus shorten ion transport pathways. However, there is a lack of research related to proton conductivity in iCONs loaded with PA. To address this, we prepared three functionalized guanidinium-based iCONs using a solvothermal condensation reaction between guanidinium amine (TG) and functionalized terephthaldehyde (Da, Dha, and Dma). PA was also incorporated into the iCON structure via ex situ loading to observe its effects on proton conduction performance. The results showed that both the iCONs and PA-iCONs were highly stable in water, organic solvents, acidic and basic media. Amongst these PA-iCONs, one with hydroxyl-functionalization (PA-DhaTG) displayed high proton conductivity at 90 degrees C and 95% relative humidity due to a Grotthuss mechanism for protons. These functionalized guanidinium-based iCONs could prove useful for applications in energy conversion devices.
Keywords: chemical stability; Functionalized pore interior; Guanidinium group; ionic covalent organic nanosheets; proton conductivity

UV-modified polydopamine zincophilic protective layer for durable and alkaline-stable zinc anodes in zinc-air batteries - Kurian, Maria; Pandikassala, Ajmal; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2025)
Rechargeable zinc-air batteries (ZABs) are promising for flexible energy storage due to their high specific energy, safety, and cost-effectiveness. However, the snags of the zinc (Zn) anode, like ineluctable passivation and dissolution in strongly alkaline electrolytes, limit the discharge and cycling performance of the battery. Electroless plating can be employed to coat the Zn foil with a polydopamine (PDA) layer, leveraging PDA's strong adsorption on the Zn via bidentate bonds. Due to PDA's poor stability in alkaline media, ultraviolet (UV)-induced secondary modifications are conducted to obtain Zn@PDA-UV electrodes with enhanced mechanical and chemical stability. The Zn@PDA-UV layer regulates Zn dendrite growth and suppresses hydrogen evolution and passivation. The zincophilic groups on the Zn@PDA-UV anode suppressed the zincate cross-over, enhancing the recyclability of the ZABs. When paired with commercial catalysts to assemble alkaline ZABs, the battery displayed excellent cycling stability of 75 h. A highly stable anion-conducting polymer electrolyte membrane (PXM) was prepared from the polymer blend of polyvinyl alcohol (PVA), xanthan gum, and METAC monomers to tailor a high-performing flexible ZAB with suppressed zincate crossover. The flexible ZAB, integrating the modified Zn anode and PXM, shows a stable cycling profile under various bending angles, demonstrating excellent mechanical and electrochemical durability.